Development of contextual e-magazine on circulatory system material for eleventh graders - Yogi Nabilla Fitra; Abdul Razak; Z. Zulyusri; Elsa Yuniarti (University of Muhammadiyah Malang, 2025)
Electronic teaching materials have an important role in improving the quality of learning, making learning more interactive, and making the learning process more flexible and productive. The development of the increasingly sophisticated era, technology, information, and communication have also developed and have an impact on learning media, initially educators used print media as a tool in the learning process, then educators combined technological developments with learning media, so that electronic learning media were created, one of which was electronic teaching materials in the form of e-magazines. This study aims to produce contextual e-magazine learning media for circulatory system material for class XI high school students that are valid and practical. The method in this study is to use the Plomp model development method. The development stage of this model begins with the initial investigation stage (preliminary research), the development or prototyping phase, and the assessment phase. The instruments used in this study were validity and practicality assessment sheets. Based on the results and discussions conducted, it was concluded that the contextual e-magazine based on circulatory system material for grade XI high school students developed in this study has achieved a validation value of 97.27% with very valid criteria and a practicality value of 96.64% with very practical criteria so that it is suitable for use as a biology teaching material for grade XI high school students.